2016
DOI: 10.1182/blood.v128.22.2753.2753
|View full text |Cite
|
Sign up to set email alerts
|

Role of Wnt/β-Catenin Signalling in Acute Myeloid Leukemia (AML) Cell Response to Chemotherapy

Abstract: Background: Growing evidences from both preclinical and clinical investigations reveal the critical role of Wnt signalling for the development of many cancers and for their response to chemotherapy. Although recent studies suggest that aberrant Wnt signalling can be involved in the neoplastic myeloid cell growth, the contribution of the Wnt/β-catenin pathway to AML survival and chemoresistance is still unclear. Aims: In this study, we investigated the contribution of WNT/β-CATENIN signalling to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Aiming to further decode the molecular mechanism underlying the higher anti-neoplastic effect of combined DAC and SAHA observed in our study, we postulated that the combinatorial treatment will modify the expression of Wnt/β-catenin and PI3K/AKT signaling pathways. The upregulation of these two signaling pathways is detectable in a high percentage of AML samples, and they have been implicated in the induction and progression of various cancers, including AML [35,60,61]. Our results showed that among the assayed proteins-pPI3K, pAKT, Wnt1, pGSK3, and p-βcatenin-SAHA treatment significantly upregulated pPI3K and pAKT expression, and the combination treatment significantly upregulated pGSK3 expression in U937 cells relative to control cells.…”
Section: Discussionmentioning
confidence: 60%
“…Aiming to further decode the molecular mechanism underlying the higher anti-neoplastic effect of combined DAC and SAHA observed in our study, we postulated that the combinatorial treatment will modify the expression of Wnt/β-catenin and PI3K/AKT signaling pathways. The upregulation of these two signaling pathways is detectable in a high percentage of AML samples, and they have been implicated in the induction and progression of various cancers, including AML [35,60,61]. Our results showed that among the assayed proteins-pPI3K, pAKT, Wnt1, pGSK3, and p-βcatenin-SAHA treatment significantly upregulated pPI3K and pAKT expression, and the combination treatment significantly upregulated pGSK3 expression in U937 cells relative to control cells.…”
Section: Discussionmentioning
confidence: 60%
“…Transcriptomic and proteomic approaches, such as flow cytometry, ELISA, Western immunobloting, and mass spectrometry, showed in MSCs the enrichment in both canonical and non-canonical Wnt pathway components (Kuljanin et al, 2017). Using phosphospecific antibodies, we observed that Ser33/37/Thr41-phospho β-catenin (inactive) is totally absent in MSC cell lysate, thus suggesting that the Wnt/β-catenin is fully active in MSCs (Takam Kamga et al, 2016b;Wang et al, 2019). The requirement of a functional β-catenin-independent Wnt signaling, such as Wnt/Ca 2+ , Wn/Jnk, Wnt/Ryk, Wnt/Ror2, was also described in MSCs (Qiu et al, 2011;Qu et al, 2013;Jeong et al, 2020).…”
Section: The Wnt Signaling In Mscsmentioning
confidence: 85%
“…Accordingly, the addition of exogenous ligands of the two pathways, such as Jagged-1 or DLL-1 (Notch signaling), and Wnt3a (canonical Wnt signaling), to cultures of purified primitive human blood progenitors induces selfrenewal, survival and expansion of stem cells provided with pluripotent repopulating capacity in mouse models (Karanu et al, 2000;Willert et al, 2003;Delaney, 2005). Our and other groups have thoroughly described the expression of Notch and Wnt signaling in MSCs (Kamdje et al, 2011;Kamdje et al, 2012;Takam Kamga et al, 2016b), but other MSC-derived stromal components, including osteoblasts, and endothelial cells, can be the source of paracrine Wnt and Notch signaling in the BM (Nemeth et al, 2009;Wang et al, 2016). Moreover, MSCs can reconstitute the complete human BMME in irradiated mice (Muguruma et al, 2006) and therefore improve HSC engraftment following transplantation (Zhao et al, 2019).…”
Section: Msc-derived Notch and Wnt Signaling Pathways In Hematopoiesismentioning
confidence: 99%
See 2 more Smart Citations